Modifying UiO-series metal-organic frameworks for fuel-forming photocatalysis - Ng, BKY (2024)
Metal-Organic Frameworks (MOFs) are porous structures built from metal-oxo clusters and organic linkers, and have recently emerged as a new class of inorganic material for various applications. These materials have wide chemical tuneability and high surface area, which has given rise to a wide range of applications. Specifically, the Universitet i Oslo (UiO) series have attracted much interest in the field of photocatalysis due to the strong ionic interaction between the highly charged Zr4+ and O2- in the zirconium building blocks and terephthalic acid.